Peningkatan Hasil Belajar PA-Katolik Melalui Model Pembelajaran Problem Based Learning (PBL) pada Peserta Didik Kelas III Fase B di SD Negeri 06 Emang Bemban - Johan Wahyudi; Dicky Aprianto (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to improve the learning outcomes of students in the subject of Catholic Religious Education (PA-Katolik) through the implementation of the Problem Based Learning (PBL) model for third-grade students in Phase B at SD Negeri 06 Emang Bemban. In the learning process, students often exhibit a passive tendency due to various factors, such as unengaging teaching methods, lengthy explanations, or a lack of understanding of the presented material.In light of this situation, this study was conducted to identify the characteristics of the students and seek solutions to enhance their engagement in learning. By employing the PBL model, the research findings indicate a significant increase in student activity in each cycle conducted. Through this approach, it is expected that better and more engaging learning outcomes can be achieved.